Performance Comparison of Geodrain Drainage and Gravel Drainage Layers Embedded in a Horizontal Plane - Mariusz Cholewa (MDPI AG, 2021)
Drainage materials are widely used, among other uses, in the construction of landfills. Regulations require a drainage layer in the base and a covering for the landfill. The implementation of a gravel drain requires a lot of material and financial outlays. New geocomposite materials are an alternative, and facilitate construction. The aim of the research was to compare the drainage properties of the Pozidrain 7S250D/NW8 geocomposite and gravel drainage. The model test was performed on a specially prepared test stand. The research was carried out for model #1, in which the gravel drainage was built. Model #2 had a drainage geocomposite built into it. The test results show the values of the volumetric flow rate for geodrains, with a maximum value of 40 dm3·min−1. For the gravel layer, values of up to 140 dm3·min−1 were recorded. Another parameter recorded during the damming of water by the embankment was the speed of water suction by the geosynthetic and gravel drainage; the values were 0.067 and 0.024 m3·s−1, respectively. The efficiency of water drainage through the geocomposite was sufficient. It is possible to use the slopes of the landfill for drainage, which will reduce material and financial outlays.